ROLE OF IMMEDIATE FEEDBACK OF MATHEMATICAL COMMUNICATION IN CONTEXTUAL TEACHING AND LEARNING - Zulfa, Aulia (Journal of the Indonesian Mathematics Education Society, 2019)
Immediate feedback is an appropriate strategy carried out by the teacher after evaluating student work. During this time the teacher only provides feedback with remedies and portfolio sometimes the teacher never gives feedback to students at all after learning is completed. Though feedback is actually a very important strategy in achieving optimal learning and to achieve student completeness, especially completeness in mathematical communication through the learning model of contextual teaching and learning. This is a concern of a teacher in mathematics teaching that is not in accordance with the objectives of teaching mathematics. The emphasis in this study is how is the role of immediate feedback in improving mathematical communication through learning Contextual Teaching and Learning?